Analisis Miskonsepsi Materi Siklus Air pada Peserta Didik Kelas VI di SDN Bujel 3 Menggunakan Tes Diagnostik Three Tiers - Rheina Rasicha Putri; Feris Rahma Auliya; M. Anas Thohir (Jurnal Sekolah Dasar, 2023)
The article aims to analyze the misconceptions of the water cycle material in Grade VI students at SDN Bujel 3 using the three tiers diagnostic test. Misconceptions are misunderstandings in connecting a concept with other concepts, between new concepts and concepts that already exist in students' minds, resulting in wrong concepts being formed and contrary to the conceptions of experts. The purpose of this research is to identify misconceptions that occur in class VI students at Bujel 3 elementary school regarding the water cycle material and to find out the percentage of students at Bujel 3 elementary school class who experience misconceptions about the water cycle material. The type of research we use is descriptive quantitative. The data collection technique used included a three-tier diagnostic test with 18 Grade VI students as research subjects. The results showed that most students were identified as having misconceptions with the largest percentage of misconceptions being on 2 topics, namely Evaporation (55.56%), and Infiltration (50.00%) while the topic with the lowest percentage of misconceptions was on the topic of understanding the water cycle ( 0.00%).